The Pre-chromatography Purification of Crude Oleoresin of Phaleria Macrocarpa Fruit Extracts by Using 70%-v/v Ethanol - Susiana Prasetyo S (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Phaleria macrocarpa is a native Indonesian plant which originated from Papua. The fruit posseses a high efficacy for health benefits due to the abundant content of antioxidant compounds, such as flavonoids, tanins, alkaloids, terpenoids and saponins. This research objective was to separate the various bioactive compounds in the extract (crude oleoresin) of the Phaleria macrocarpa fruit into several fractions, prior to a HPLC fraction collector, by using several selective solvents. The separation process utilized a liquid-liquid extraction method by an oscillation equipment for 1-2 hours. The extractions were carried out using F : S ratio of 1:1, at room temperature with 70%-v/v ethanol. The crude extract of each extract and raffinate was analyzed quantitatively. The quantitative analysis methods used were Obadoni and Ochuko for saponins test, n-hekxane separation for terpenoids test, and aluminium ion for flavonoids test. Folin-Ciocalteu and Sreevidya and Mehrotra methods were utilized for tannins and alkaloids tests, respectively. Meanwhile, the antioxidant activity was measured by DPPH method. The experimental results showed that the hexane fraction (first partition) was able to extract the resin component and selective enough to extract terpenoid groups (steroids) with Kd = 9.5960. The second partition, using chloroform solvent was not successful because of all the phytochemical components were evenly distributed in both fractions. Meanwhile, n-butanol fraction (third partition) selectively extract a large amount of flavonoid groups with Kd = 5.4880 but none of saponin was detected in this fraction. Flavonoid groups was found as the dominant component in the fruit extract contributed to the high antioxidant activity.